An exploration of the health promotion activities implemented by universities: have we got the right balance?. Issue 6 (2nd November 2022) - Mcdonald, Hayden; Delaney, Deborah; Gould, Ryan; Vecchio, Nerina
ABSTRACT: Guidelines for implementing health promotion programmes within university settings outline key action areas for addressing health concerns. Further guidance is needed to help manage specific health promotion activities according to the needs and resources available to universities. Decisions about allocating resources to improve employee health depend on diverse factors such as the workplace, industry, country, and employee. A more nuanced understanding of health promotion programme implementation should help universities address the alarming rates of occupational stress reported among employees. This present study develops a taxonomy to help universities implement appropriate activities. Content analysis and interview findings highlight the importance of communication between workplaces and employees to determine the motivations for adopting health promotion activities. Collaboration between an extensive network of stakeholders will likely ensure that appropriate activities are available, supported, and implemented to target employee health concerns.